2014
DOI: 10.1159/000362825
|View full text |Cite
|
Sign up to set email alerts
|

Early Childhood Caries Is Associated with Genetic Variants in Enamel Formation and Immune Response Genes

Abstract: Early childhood caries (ECC) is a chronic, infectious disease that affects the primary dentition of young children. It is the result of an imbalance of risk factors and protective factors that influence the disease. The aim of this study was to assess genetic and environmental factors that may contribute to ECC. Two hundred and fifty-nine unrelated children were evaluated using a cross-sectional design. Data on oral habits were obtained through a questionnaire, and caries experience data were collected by clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
67
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(82 citation statements)
references
References 31 publications
12
67
1
2
Order By: Relevance
“…4 On the other hand, Abbasoğlu et al found no association between the same AMELX polymorphism and caries susceptibility in Turkish children. 5 There were also no associations between amelogenin genetic variants and dental caries experience in other studies performed on Polish, French, Caucasian, and Japanese populations. [6][7][8]12 However, studied SNPs for AMELX gene and the age of children were different from those chosen for our study, also the studied populations were heterogeneous regarding demographic origins and cultural diversity.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…4 On the other hand, Abbasoğlu et al found no association between the same AMELX polymorphism and caries susceptibility in Turkish children. 5 There were also no associations between amelogenin genetic variants and dental caries experience in other studies performed on Polish, French, Caucasian, and Japanese populations. [6][7][8]12 However, studied SNPs for AMELX gene and the age of children were different from those chosen for our study, also the studied populations were heterogeneous regarding demographic origins and cultural diversity.…”
Section: Discussionmentioning
confidence: 84%
“…21 Abbasoğlu et al, Deeley et al and Slayton et al did not find association between AMBN genetic variants and caries experience in Turkish, Guatemalan-Mayan and mixed populations, respectively, although Slayton et al noticed that out of the children who participated in the study, Caucasian children had the greatest severity of the disease. 5,7,11 On the other hand, Patir et al observed an overrepresentation of the minor T allele in rs34538475 in caries experienced individuals in comparison to controls, regardless of the stage of the disease. 4 In our study, however, we observed an opposite association, as both the minor T allele (p < 0.0001) and the minor TT homozygote (p < 0.0001) were overrepresented in controls in comparison to cases with caries, which supported the T allele as a protective variant.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations